Chemical and genetic variation in feral Cannabis sativa populations across the Nebraska climate gradient. (August 2022) - Busta, Lucas; Dweikat, Ismail; Sato, Shirley J.; Qu, Haolin; Xue, Yong; Zhou, Bangjun; Gan, Lu; Yu, Bin; Clemente, Thomas E.; Cahoon, Edgar B.; Zhang, Chi
Abstract: Cannabis sativa is a versatile crop that can be cultivated for fiber, seed, or phytochemicals. To take advantage of this versatility and the potential of Cannabis as a feedstock for the bioeconomy, genomics-enabled breeding programs must be strengthened and expanded. This work contributes to the foundation for such by investigating the phytochemistry and genomics of feral Cannabis populations collected from seventeen counties across the climate gradient of Nebraska. Flower tissue from male and female plants (28 total) was studied using (i) gas chromatography-mass spectrometry to assess cannabinoid profiles and (ii) RNA sequencing to determine transcript abundances. Both male and female flower tissues produced cannabinoids, and, though the compounds were more abundant in female flower tissue, the primary cannabinoid in both was usually cannabidiol. The expression of genes that mediate early steps on the cannabinoid biosynthetic pathway were upregulated in female relative to male flowers, suggesting that female versus male flower tissue cannabinoid abundance may be controlled at least in part at the transcriptional level. DNA sequencing was used to place feral Cannabis plants from Nebraska into a previously described genomic context, revealing that all the plants studied here are much more similar to previously characterized hemp-type Cannabis plants than to drug-type Cannabis plants, at least at the genetic level. This work provides foundational phytochemical knowledge and a large set of high-quality single nucleotide polymorphism markers for future studies of feral Nebraska Cannabis . Graphical abstract: Image 1 Highlights: Feral Nebraska Cannabis is genetically hemp-like and exhibits three chemotypes.